The Effect of Cognitive–Behavioral Play Therapy on Improvements in Expressive Linguistic Disorders of Bilingual Children - Rezaeerezvan, Shahrzad; Kareshki, Hossein; Pakdaman, Majid (Frontiers in Psychology, 2022)
The present study attempted to investigate the effect of cognitive-behavioral play therapy (CBPT) on the improvements in the expressive linguistic disorders of bilingual children. The population consists of all bilingual children with expressive linguistic disorders studying in preschools. Considering the study’s objectives, a sample of 60 people, in three groups (experimental, control, and pseudo-control), were selected using WISC, TOLD, and clinical interviews. The experimental group members participated in CBPT training sessions. The training consisted of twelve 90-min sessions, three times per week programs held every other day. The pseudo-control group received training different from play therapy. The experimental group members were subjected to the follow-up test 2 months after the end of the intervention. All three groups sat the TOLD3 test before and after the experiment. Data analysis was carried out using ANCOVA. The results of data analysis suggested that CBPT can improve the expressive language disorders of bilingual children.